2011
DOI: 10.1038/npp.2011.161
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Brain Metabolism in Resistant Depression and Response to Transcranial Magnetic Stimulation

Abstract: Neuroimaging studies of patients with treatment-resistant depression (TRD) have reported abnormalities in the frontal and temporal regions. We sought to determine whether metabolism in these regions might be related to response to repetitive transcranial magnetic stimulation (TMS) in patients with TRD. Magnetic resonance images and baseline resting-state cerebral glucose uptake index (gluMI) obtained using 18 F-fluorodeoxyglucose positron emission tomography were analyzed in TRD patients who had participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…Reduced GMV in vmPFC has been correlated with hyperactivation in other regions implicated in emotion processing in several studies investigating both structural and functional changes (Scheuerecker et al, 2010;Wagner et al, 2008;Paillere Martinot et al, 2011). The putative connectivity between vmPFC and temporal lobes, including amygdala is suggested by our covariance analysis in WMV but is also supported by a recent study demonstrating a significant covariance of GMV between amygdala and vmPFC (Singh et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Reduced GMV in vmPFC has been correlated with hyperactivation in other regions implicated in emotion processing in several studies investigating both structural and functional changes (Scheuerecker et al, 2010;Wagner et al, 2008;Paillere Martinot et al, 2011). The putative connectivity between vmPFC and temporal lobes, including amygdala is suggested by our covariance analysis in WMV but is also supported by a recent study demonstrating a significant covariance of GMV between amygdala and vmPFC (Singh et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
“…The UF represents a major white matter bundle linking orbitofrontal regions with amygdala, thus representing critical components of the frontotemporal network that is central for affective processing and which is thought to be dysfunctional in MDD (Paillere Martinot et al, 2011;Price and Drevets, 2012;Von Der Heide et al, 2013). Prior ROI work in this sample has shown that rMDD patients have increased left amygdala volume when compared to HC (non-significant trend for Two clusters of voxels result from the comparison between subjects that have been diagnosed with a major depressive disorder (MDD), including current or remitted depressed, and healthy controls (HC).…”
Section: Wmv Covariance Analysismentioning
confidence: 99%
“…In line with the TMS findings described above, using FDG-PET, Martinot et al (2011) also found decreased glucose uptake in prefrontal cortical regions and in the anterior cingulate cortex in both responders and non-responders to high-frequency repetitive TMS treatment in the prefrontal cortex. Particularly, non-responders had lower levels of glucose reuptake in the left ACC, bilateral insula, and left orbitofrontal and dorsolateral PFC (Martinot et al, 2011).…”
Section: Insular Cortex Activity In Mddsupporting
confidence: 73%
“…Particularly, non-responders had lower levels of glucose reuptake in the left ACC, bilateral insula, and left orbitofrontal and dorsolateral PFC (Martinot et al, 2011). In addition, non-responders also had lower gray matter volume in the left ACC, and prefrontal cortical regions (orbitofrontal, ventro-, and dorsolateral PFC; Martinot et al, 2011).…”
Section: Insular Cortex Activity In Mddmentioning
confidence: 99%
“…However, given the differences observed between healthy controls and sufferers of depression, replication of results obtained in depression studies cannot necessarily be anticipated. Numerous studies highlight changes in functional connectivity and grey and white matter density, of cortical and subcortical structures (Amico et al 2011;Chang et al 2011;Davis 2004;Lacerda et al 2004;Martinot et al 2011;Taylor et al 2004), which would influence current density and flow through prefrontal structures (Shahid et al 2013).…”
Section: Introductionmentioning
confidence: 99%